Keterpaduan Kearifan Lokal dan Islam dalam Kehidupan Masyarakat Petani di Desa Bulutellue - Abdul Rahman (Pinisi Journal of Sociology Education Review, 2023)
When religious teachings fit in a civilized community, will be the attraction between the interests of religion on the one hand with cultural interests on the other. The relationship between Islam and local culture is leaving tug issues often provoke tension. On the one hand, the local culture is considered no more than a parasite for religion and therefore always removed. At the same time religion was regarded as the scourge of the local culture that threatens its existence. In the Muslim community village relegius relationship lasted Bulutellue among populations that interact and relate because based on the existence of an equation in achieving the goals that they both believe in the truth and tied to a culture that they produce themselves, implemented and adhered to itself. Sociologically, indigenous peoples Bulutellue in life tend to promote a sense of brotherhood, tolerance, cooperation prioritizes massively (collectively) in a variety of ways. This study aims to determine the depth of Muslim society dialectic pattern Bulutellue village with local culture, and the factors underlying sosioantropologis. This research is qualitative research is the role of the researcher as the main instrument in the research process. Using social definition paradigm that directs attention and how social actors define social situations as well as the effects of the social definitions for maintaining the action and interaction.